2012
DOI: 10.1093/pcp/pcs149
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis ABCB21 is a Facultative Auxin Importer/Exporter Regulated by Cytoplasmic Auxin Concentration

Abstract: The phytohormone auxin is critical for plant growth and many developmental processes. Members of the P-glycoprotein (PGP/ABCB) subfamily of ATP-binding cassette (ABC) transporters have been shown to function in the polar movement of auxin by transporting auxin over the plasma membrane in both monocots and dicots. Here, we characterize a new Arabidopsis member of the ABCB subfamily, ABCB21/PGP21, a close homolog of ABCB4, for which conflicting transport directionalities have been reported. ABCB21 is strongly ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
124
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
2

Relationship

5
5

Authors

Journals

citations
Cited by 135 publications
(128 citation statements)
references
References 37 publications
(58 reference statements)
3
124
0
1
Order By: Relevance
“…Auxin exporters are primarily represented by plasma membrane localized PINs (so-called long PINs, see below) and members of the ABCB family, which have so far all been found to be plasma membrane-embedded [6,[25][26][27]. However, it should be mentioned that recently ABCB4 and ABCB21 were characterized as facultative importer/exporters whose transport directionality seems to be triggered by intracellular auxin levels [28].…”
Section: Auxin Transport Across Biological Membranesmentioning
confidence: 99%
“…Auxin exporters are primarily represented by plasma membrane localized PINs (so-called long PINs, see below) and members of the ABCB family, which have so far all been found to be plasma membrane-embedded [6,[25][26][27]. However, it should be mentioned that recently ABCB4 and ABCB21 were characterized as facultative importer/exporters whose transport directionality seems to be triggered by intracellular auxin levels [28].…”
Section: Auxin Transport Across Biological Membranesmentioning
confidence: 99%
“…It is possible that eukaryotic ABC "importers" present the same fold as "exporters", but have evolved an inverse affinity switch that allow them to transport the substrate inwards. Indeed, it has been demonstrated that some plant ABC transporters are capable of switching between the importer and exporter mode depending on substrate concentrations [68,69].…”
Section: General Structural Features Of Abc Transportersmentioning
confidence: 99%
“…ABC transporters are classified as importers (those that mediate inward translocation of substrates into the cell) or exporters (those that facilitate extrusion of solutes from the cell). The former are predominantly present in prokaryotes [15][16][17], whereas the latter are found in both prokaryotes and eukaryotes [18]. ABC importers can be grouped into 2 further subtypes based on their topology in the membrane [19,20].…”
Section: Abc and Ecf Transporters Abc Transportermentioning
confidence: 99%